(untitled) (The Research of Medical Science Review, 2025)
Gestational Diabetes Mellitus is one of the most serious public health problems, which may result in poor maternal and fetal outcomes. This study evaluates the effectiveness of nutritional interventions in improving glycemic control and perinatal outcomes in pregnant women with GDM in Karachi, Pakistan. 300 pregnant women with a diagnosis of GDM were enrolled and randomly assigned to the intervention group that received individualized nutritional guidance and dietary adjustment and to the control group receiving standard treatment. Glycemic levels were followed up, and perinatal outcomes like birth weight, preterm births, and neonatal complications were noted. Analysis was carried out using SPSS with paired t-tests and regression models. Results emerged that the intervention group achieved significant improvement in glycemic control with a p-value of less than 0.05 and also accounted for fewer adverse perinatal outcomes as compared with the control group. Thus, this study underlines the necessity of incorporating dietary interventions into the management strategy of GDM, especially within resource-limited settings.